Complications of the Climate Change Narrative within the Lives of Climate Refugees: Slow Causality and Apocalyptic Themes - Mascia, Raphaella (Consilience, 2020)
With projections of rapidly increasing numbers of climate refugees in the next decades, the discourse surrounding climate refugees becomes ever more pertinent within the field of sustainable development and the public sphere. I offer an alternative analysis of the processes which surround “knowing” and “defining” climate refugees by employing an interpretive framework which disseminates the term “narrative” according to Jean François Lyotard’s The Postmodern Condition: A Report on Knowledge. In the discourse surrounding climate refugees, two main narratives interact with each other: the dominant climate change narrative and the individual narratives of climate refugees themselves. I contend that the dominant narrative of climate change complicates the narratives of climate change refugees through specific characteristics of climate change discourse, specifically, the temporal characteristics of slow causality and apocalyptic themes as evinced in two case studies, one in the small town of Shishmaref, Alaska and the other in the Maldives. Through researching and examining the thematic elements featured in narration, we gain a fuller comprehension of the personal narratives of climate refugees. The dominant climate change discourses permeate almost all environmental issues, and therefore, the field of sustainable development continuously confronts and interacts with such discourses. Furthermore, one aspect of sustainable development involves the ongoing circumstances of forced migration due to climate change. Illuminating the ways in which the dominant climate change narrative reduces the personal narratives of climate refugees compels us to look towards climate refugees themselves as sources for their own narratives instead of permitting the dominant narratives to overshadow their experiences.